Risk Communication During COVID-19 - Abrams, Elissa M. (J Allergy Clin Immunol Pract, 2020)
During the unprecedented times caused by the novel coronavirus disease 2019, there is rapidly evolving information and guidance. However, a focus must also be on proper and effective risk communication. This is especially the case during pandemics that have high rates of infection, significant morbidity, lack of therapeutic measures, and rapid increases in cases, all of which apply to the current coronavirus disease 2019 pandemic. A consequence of poor risk communication and heightened risk perception is hoarding behavior, which can lead to lack of medications and personal protective equipment. One potential way to ensure appropriate risk communication is using social media channels, and ensuring an ongoing consistent media presence. Another important step is to include all stakeholders including members of the allergy community in broader public health messaging. As we continue to face unprecedented times in the allergy community, an understanding and appreciation of risk communication will be essential as we communicate with, and inform, our patients, and our colleagues, moving forward.